2010
DOI: 10.1111/j.1360-0443.2010.03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary care-based intervention to reduce at-risk drinking in older adults: a randomized controlled trial

Abstract: Aims-To examine whether a multifaceted intervention among older at-risk drinking primary care patients reduced at-risk drinking and alcohol consumption at 3 and 12 months. Design-Randomized controlled trial.Setting-Three primary care sites in southern California.Participants-Six hundred thirty-one adults aged ≥ 55 years who were at-risk drinkers identified by the Comorbidity Alcohol Risk Evaluation Tool (CARET) were randomly assigned between October 2004 and April 2007 during an office visit to receive a bookl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 31 publications
5
103
0
3
Order By: Relevance
“…The data from this trial compare favorably with those from the three other published trials in primary care aimed at reducing some aspect of alcohol consumption among older adults (Fink et al, 2002a;Fleming et al, 1999;Moore et al, 2011). Project GOAL (Guiding Older Adult Lifestyles) was a randomized trial testing the effi cacy of brief physician advice and follow-up nurse calls in reducing alcohol use in problem drinkers ages 65 and older (Fleming et al, 1999).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The data from this trial compare favorably with those from the three other published trials in primary care aimed at reducing some aspect of alcohol consumption among older adults (Fink et al, 2002a;Fleming et al, 1999;Moore et al, 2011). Project GOAL (Guiding Older Adult Lifestyles) was a randomized trial testing the effi cacy of brief physician advice and follow-up nurse calls in reducing alcohol use in problem drinkers ages 65 and older (Fleming et al, 1999).…”
Section: Discussionsupporting
confidence: 49%
“…However, more than half of the participants in the Fink et al (2005) study were nonhazardous drinkers at baseline, and unmeasured site heterogeneity may have confounded the associations between the treatment arm and patient outcomes. Participants in the Healthy Living as You Age (HLAYA) study were those identifi ed as at-risk drinkers at baseline using the CARET (Moore et al, 2011). All participants in the intervention arm received baseline personalized reports and physician feedback as well as health educator telephone calls at 2, 4, and 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence, based on the use of a modified ARPS system, suggests that providing information on recommended drinking limits to older adults may be enough to cause large reductions in both at-risk drinking and amount of alcohol use, 32 and similar results were found in the Santa Monica trial of the ARPS system. 10 There are many reasons why physicians do not screen their older patients for alcohol misuse or, if they do, why they rely primarily on self-reported alcohol consumption.…”
Section: Discussionmentioning
confidence: 65%
“…Interdisciplinary, broad, or multifaceted mental healthcare management programs, either with primary care patients or male veterans, were studied in more RCTs (Bartels et al, 2004;Oslin et al, 2004;Moore et al, 2010;Ettner et al, 2014;Vrdoljak et al, 2014). Disappointingly, only two RCTs (Moore et al, 2010;Ettner et al, 2014) found a statistically significant advantage of intervention over CAU.…”
Section: Treatment Of Alcohol Use Disorders In the Elderly: An Overvimentioning
confidence: 99%